Висвітлення партизанського руху на українських землях у роки Великої Вітчизняної війни: сучасна історіографія - Свинаренко, Н.О. (Історичний архів. Наукові студії, 2013)
Проаналізовано у російській науковій історичній думці проблеми висвітлення
партизанського руху на території сучасної України у роки Великої Вітчизняної війни.
Зазначено, що проблемні аспекти діяльності радянського партизанського руху на
окупованій Україні певною мірою притаманні сучасній російській історіографії. Виявлено,
що біографії найвидатніших лідерів партизанського руху є цікавими для сучасних
російських істориків і вони охоче досліджують маловивчені та недосліджені до наших
днів деякі сторони життя цих легендарних людей, помічено досить значні розбіжності у
цифрових відомостях українських та російських істориків стосовно показнику
масовості тодішнього партизанського руху. Доведено, що у багатьох російських
підручниках та навчальних посібниках ці події описані досить побіжно і поверхнево, іноді
стиль викладу мало відрізняється від того, як характеризували партизанський рух у
традиційному викладі, адаптованому вимогам правлячої ідеології радянської епохи.
Також доведено, що для сучасної пострадянської російської історичної наукової думки
притаманне висвітлення раніше заборонених життєвих реалій щоденних партизан-
ських буднів. Проанализировано в российской научной исторической мысли проблемы освещения
партизанского движения, его экономических и политических аспектов, на территории
современной Украины в годы Великой Отечественной войны. Отмечено, что
проблемные аспекты деятельности советского партизанского движения на
оккупированной Украине в некоторой степени присуще современной российской
исторической литературе. Выявлено, что биографии выдающихся лидеров
партизанского движения интересны для современных российских историков и они
охотно исследуют малоизученные и неисследованные до наших дней некоторые
стороны жизни этих легендарных людей, замечено довольно значительные расхождения в
цифровых сведениях украинских и российских историков в отношении массовости
тогдашнего партизанского движения. Доказано, что во многих российских учебниках и
учебных пособиях эти события описаны достаточно бегло и поверхностно, иногда
стиль изложения мало отличается от того, как характеризовали партизанское
движение в традиционном изложении, адаптированном требованиям правящей
идеологии советской эпохи. Также доказано, что для современной постсоветской
российской исторической научной мысли присуще освещения ранее запрещенных
жизненных реалий ежедневных партизанских будней. The article studies the Russian scientific historical experience of the problem by comparing
the modern Ukrainian historiography and the modern Russian historical literature devoted to the
partisan movement having been during the years of the Great Patriotic War on the territory of
Ukraine. The work also aims at defining the degree of examination of this problem by Russian
historiography. Obviously, the problematical aspects of activity of the Liberation movement in
Ukraine occupied by the Nazis may be found in the modern Russian historical literature. Despite
the Soviet historiography, where the Partisan Movement is represented as the heroic, patriotic,
international phenomena, in the modern Ukrainian historical non-fiction literature it is shown as
unembellished one, sometimes – as inconsistent phenomena. The biographies of the most
prominent leaders of the Partisan movement are interesting for some modern Russian
Випуск 11
41
historians, publicists. They inspiringly analyze aspects of living, which have poorly researched
till present days, and activity, which is unexamined, of these famous, charismatic persons. The
essential differences between the numerical data given by the Ukrainian and the Russian
historians, who tried analyzing indicators of scale of Partisan movement within the territory
occupied by the Nazis, have been found. There are also lots of Russian textbooks, manuals,
courses of lectures, scientific, science and popular, and journalistic articles devoted to those
events, which have not been deeply studied enough. Sometimes view proposed by authors
differences by a little from when the Partisan movement was shown according to the traditional
format, which was typical for the State ideology of Soviet period. In the modern Russian
historiography the new theme of research has appeared, in other words, the historians and
publicists tried investigating such aspects of Partisans’ life as amorality, drinking making
Partisans cruel to their own people. Such daily aspects of Partisan movement, on the one hand,
as bloody beating, and, then, torturing the bloodstained and humble victims of war violence,
and, on the other hand, as drinking, assaults, burning people, cutting organs from victims’
bodies (not relating to the Nazis, but to country dwellers of the lands occupied by the Nazis.
The following has been proved: the modern post-Soviet Russian historical sought
concentrates on an examination of the realities of everyday and hourly partisan problems. The
following has been shown: now, the analyze before unedited diaries, letters, other documents
belonging to the famous partisan leaders, due to whom this really patriotic movement in the
Ukrainian lands in years of the Great Patriotic war has become unembellished, is actual for the
Russian scholars. The war problems (including psychological ones), biographies of the famous
partisan leaders, real scale of effectiveness and features of the movement for liberty from the
Nazis in different parts of the country etc. need more careful examination.